2015
DOI: 10.4338/aci-2014-10-ra-0098
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Parent Perspectives on Use of Patient Portals for Their Children’s Health Care

Abstract: Current use of patient portals by parents is low. Only about half of parents currently using or likely to use a portal perceive value in using portals for certain tasks, which suggests that providers will need to continue traditional communication mechanisms to reach their entire patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…In literature, there is some skepticism about the influence of a patient portal on the security and privacy of health data and the total costs of health care [ 13 , 41 , 42 ]. People are mostly interested in test results, medication schemes, immunization records, and a history of medical visits and procedures [ 21 , 43 ]. These findings are consistent with ours, where about three-quarters of respondents believed that a patient portal could improve the doctor-patient communication, the understanding and sense of control of their health, and the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there is some skepticism about the influence of a patient portal on the security and privacy of health data and the total costs of health care [ 13 , 41 , 42 ]. People are mostly interested in test results, medication schemes, immunization records, and a history of medical visits and procedures [ 21 , 43 ]. These findings are consistent with ours, where about three-quarters of respondents believed that a patient portal could improve the doctor-patient communication, the understanding and sense of control of their health, and the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Parents have expressed interest in viewing vaccination records as part of a PHR. 116 , 117 At least one study has demonstrated an increase in influenza vaccination in adults through the use of PHR-based alerts. 118 …”
Section: Introductionmentioning
confidence: 99%
“…One national survey found that only 59% of those eligible enrolled in a portal. 2 Absence of perceived need, lack of time, and ignorance of availability are the reasons reported in this survey. Unfamiliarity with portal usage is also a common concern and sociodemographic disparities were reported in signing up and activation 3 of such patient portals.…”
Section: Introductionmentioning
confidence: 87%